Prompt and precise identification of various sources of infection in response to the prevention of malaria re-establishment in China - Jianhai Yin; He Yan; Mei Li (BMC, 2022)
Abstract Prompt and precise diagnosis of patients is an essential component of malaria control and elimination strategies, it is even more vital for the prevention of malaria re-establishment in the post elimination phase. After eliminating malaria in China, the strategy for prevention of malaria re-establishment was updated in a timely manner from the elimination strategy focusing on each case/focus to the prevention of re-establishment focusing on timely identification of the source of infection. However, there are numerous challenges, such as the persistent large number of imported malaria cases, the long-term threat of border malaria, unknown levels of asymptomatic infections and Plasmodium falciparum HRP2/3 gene deletions, and the continuous spreading of antimalarial drug resistance. Meanwhile, the detection capacity also need to be further improved to meet the timely detection of all sources of infection, otherwise it is bound to occur introduced malaria cases and malaria re-establishment in the presence of malaria vector mosquitoes. Therefore, it is necessary to continuously strengthen the malaria detection competency at all levels, promote the research and development on the malaria parasitological testing technologies, thus improving the timely detection of various sources of infection, and preventing the re-establishment of malaria. Graphical abstract